Primary School Teachers' Observations on Basic Predictors of Initial Pupils' Literacy - Comparative Approach - Višnja S. Mićić; Želimir Ž. Dragić; Slaviša V. Jenjić (University of Belgrade, Teacher Education Faculty, 2024)
The paper presents the results of a comparative analysis of the observations of the lower primary school teachers in the Republic of Srpska and the Republic of Serbia, which refer to the basic predictors of successful initial literacy of pupils of the same age in two partially different education systems. The goal of the research is to identify the predictors of the successful initial reading and writing skills that need to be encouraged more during the preparatory preschool program in the Republic of Serbia, i.e., the first grade of primary school in the Republic of Srpska. We grouped the predispositions into two conditional modalities, namely: a) phonological awareness and b) graphomotor preparation of students for initial literacy. A total of 257 teachers from the Republic of Serbia and 253 teachers from the Republic of Srpska participated in the research sample. A survey questionnaire was used in the research. The Alpha Cronbach reliability coefficient of the questionnaire was α=0,89. The answers of the respondents from the Republic of Serbia have an arithmetic mean value of M=30,14, which is lower than the answers of the primary school teachers from the Republic of Srpska, where this value is M=34,64. The fact that this is a statistically significant difference in arithmetic means can be seen in the obtained value of t= -10,48 at the p=0,05 level. The analysis of the obtained results calls for a discussion about the place of the initial literacy in the preschool and primary school curricula in both education systems, considering that in each of the variables a higher value of the answers appears in the respondents from the Republic of Srpska.